PERANCANGAN DAN UJI FUNGSI SISTEM PEMBERSIH KANDANG SAPI TIPE PENGIKIS LANTAI MENGGUNAKAN SOROK MEKANIK - Ipung Kurniawan; Pujono; Pribadi, Joko Setia; Dian Prabowo (Politeknik Negeri Cilacap, 2024)
The floor scrapping method for cowshed cleaning systems has been widely applied on several modern farms today with the aim of making it easier for farmers to clean the cowshed. The mechanical design of the motor-driven scraper aims to facilitate the cowshed and save human energy. The design method uses James H. Earle method and is continued by carrying out the production process for the cowshed cleaning systems. This system works using a chain to pull the scraper so that it moves to scrape dirt on the floor by pushing it, so that work that was previously done manually can be done more easily with the help of this tool. The designed tool has dimensions of 1000 mm x 500 mm x 300 mm, while the mechanical beam design has dimensions of 700 mm x 200 mm x 3 mm. Based on the calculation results, bending stress data was obtained of 20.534 N/mm2 for the frame and 41.476 N/mm2 for the scraper. Calculation of the transmission system for the cowshed cleaning tool obtained specifications for an electric motor with a power of 0.02 HP, a pulley measuring 72.6 mm, a belt measuring 26 inches, a shaft measuring 12 mm and rolling bearings with a life of 24 years. Then, from the result of testing the frame and scraper using Solidwork software, it was found that the stress was 29.95 MPa for the frame and 67.49 MPa for the scraper. This stress value is declared safe because it is still below the permitted stress. Meanwhile, based on function testing, the most effective nozzle to use is a nozzle with an angle of 15o because it has a higher spray intensity than the others and thus has the highest cleanliness value. Based on test results, the cowshed cleaning tool obtained an average cleanliness score of 75.6 with a time of 60 seconds.